Energy-saving evaluation and control optimization of an ASHP heating system based on indoor thermal comfort. (December 2019) - Dong, Zhang; Boyi, Qu; Chunlong, Wang
Highlights: The PMV is amended by the thermal perception of rural residents in northwest China. Different indoor temperatures, water temperatures of tank and operational modes are used. The relationship between energy saving and indoor thermal comfort is deeply analyzed. Find an optimal control which can provide comfort and minimized energy consumption. Abstract: Indoor thermal comfort and energy conservation are the unity of opposites in residential buildings heating. Based on indoor thermal comfort, the energy-saving control of ASHP (Air Source Heat Pump) heating system is optimized. The PMV (Predicted Mean Votes) is amended by the thermal perception of rural residents in northwest China. Energy consumption, system efficiency, operation cost and PMV are used to evaluate the system. Different ranges of indoor temperature and control operation strategies are set up. The tested results show that the daily power consumption increases by 86.23% while the PMV rises by 1.09. When the PMV maintain between −0.03 and +0.26, the daily power consumption of intermittent operation is 14.97% lower than continuous operation. When the water temperature of tank is controlled at 40 °C, the daily power consumption is 41.84% lower than at 50 °C, the PMV can maintain in a comfortable range. It is suggested that the optimal control strategy of the ASHP heating system is intermittent operation. When the mean daily outdoor temperature is 0 °C, the indoor temperature and the water temperature of tank should be controlled at 14–16 °C and 38 °C, respectively. It can provide a new control optimization method for ASHP heating system.